EFFECT OF TRAINING AND WORK ETHIC ON EMPLOYEE PERFORMANCE - Muhammad Andi Prayogi; Cici Ayunda Putri (Proceeding International Seminar of Islamic Studies, 2022)
The research was conducted to see how the level of influence of training and work ethics on employee performance. This research uses quantitative methods and associative approaches. The associative approach is used to see the influence between two or more variables, in this study the total population was 50 respondents, the sample was a saturated sample, namely the entire population of 50 respondents. The data analysis technique is using multiple linear regression. The tool to analyze the data is by using SPSS 22. The results of this study partially show that training has a positive and significant effect on employee performance, partially positive and significant work ethic has a positive and significant effect on employee performance. Simultaneously training and work ethics have a positive and significant effect on employee performance at PT. PLN (Persero) UP2B Sumbagut.Keywords: Training, Work Ethic, Employee Performance